Using fuzzy logic for congestion control at the user-network interface of asynchronous transfer mode networks - Albrecht, Frederick Mark (Department of Electrical Engineering, 2016)
The aim of this thesis was to design a fuzzy logic controller that could be used to prevent congestion in Asynchronous Transfer Mode networks. The controller would be located at the User-Network Interface of the network and would be used to monitor the incoming traffic. The control action would be to allow conforming traffic through to the network unmodified, while tagging or dropping non-conforming traffic. Three fuzzy logic controllers are presented, the latter two being improvements on design(s) that preceded it. All three controllers are designed to police the sustainable cell rate of Variable Bit Rate (VBR) traffic sources, and take the Sustainable Cell Rate and Peak Cell Rate as input Parameters. The first two controllers require an additional parameter called the Burst Threshold, while the third controller takes the Initial Burst Size as its third traffic parameter. The controllers then continuously analyse the state of the traffic by applying a set of rules that it was given and decides whether the source is conforming or non-conforming, taking corrective action if required. The first controller included two buffers that were used to determine the state of the connection. It was however found that it would be too difficult to determine what sizes to make those buffers, and therefore that design was abandoned in favour of the second controller. The second controller eliminated the need for buffers in the design, while still being able to tag or drop non-conforming cells and allowing conforming cells through unmodified. This was done by including a token leaky bucket in the design and modifying the fuzzy sets and rule base of the fuzzy logic engine accordingly. A